'Island Life' before man: biogeography of palaeo‐insular mammals. (16th September 2016) - van der Geer, Alexandra A. E.; Lomolino, Mark V.; Lyras, George A.
Abstract: Aim: To assess the relative contributions of colonization, speciation and human activities on species richness ( S ) of mammalian communities among oceanic islands. Location: Palaeo‐islands world‐wide. Methods: We compiled species lists from published works and compared species–area and species–isolation relationships for mammalian taxa of 36 islands over three stages of community development during the late Pleistocene and Holocene: at colonization, or founding ( S f ); after in situ speciation, but before colonization by humans ( S s ); and during the Anthropocene ( S A ), that is, following human colonization and subsequent extinctions and species introductions. We used regression and correlation analyses to compare S f and S s patterns to assess the impact of speciation on the native assemblages, and compared these patterns to those expected by island biogeography theory (largely based on patterns for extant insular faunas). We then compared patterns for S s and S A to assess impacts of human activities on insular community structure. Results: Although patterns for S f were consistent with those expected based on island biogeography theory ( S f increasing with area and decreasing with isolation), patterns for S s were quite anomalous, with uncharacteristically steep log‐log slopes (high z ‐values) of the species–area relationship, and no significant influence of isolation on S s . Analyses based on contemporary assemblages ( S A ) indicated that human activities have rendered native assemblages highly depauperate, while anthropogenic introductions have inflated richness far above S s on all but the largest islands. Main conclusions: Long‐standing models of island biogeography may prove inadequate unless their conceptual domains are expanded to include the effects of all three fundamental, biogeographical processes (immigration, extinction and speciation), the impact of human activities on each of these processes, and the likelihood that, at least for very large and isolated islands, a long‐term equilibrium among these processes is seldom achieved.